A Techno-Functional Analysis of Acheulean Backed Knives from Wonderboom, South Africa. (3rd April 2023) - Caruana, Matthew V.; Lotter, Matt G.; Lombard, Marlize
ABSTRACT: We present the first techno-functional examination of backed knives from the southern African Acheulean. Our results suggest that they were opportunistically produced, although they demonstrate a unique ergonomic design that may have increased their efficiency in subsistence activities. Moreover, the frequency of backed knives at Wonderboom may be associated with possible meat harvesting at a nearby gap (Wonderboompoort) in the Magaliesberg range, which formed a bottleneck for animal herds migrating across major biome boundaries in the deep past. The Wonderboom knives might have been made on an ad hoc basis to augment butchery practices.